The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/ijerph15112472
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Black Carbon Concentrations and Atmospheric Pollution around Singrauli Coal-Fired Thermal Power Plants (India) Using Ground and Satellite Data

Abstract: The tropospheric NO2 concentration from OMI AURA always shows high concentrations of NO2 at a few locations in India, one of the high concentrations of NO2 hotspots is associated with the locations of seven coal-fired Thermal Power plants (TPPs) in Singrauli. Emissions from TPPs are among the major sources of black carbon (BC) soot in the atmosphere. Knowledge of BC emissions from TPPs is important in characterizing regional carbonaceous particulate emissions, understanding the fog/haze/smog formation, evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“… 32 , 33 Furthermore, BC concentrations reaching as high as 200 μg m –3 have been reported in transit regions in the vicinity of such thermal power plants. 34 In fact, the coupling between the BC concentrations and air mass origin, visualized using CWT maps ( Supporting Information Figure S3.c ), shows that BC at BCOB (although an order lower than expected in the vicinity of power plants; Supporting Information Figure S4 ) mostly arrived from the IGP.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“… 32 , 33 Furthermore, BC concentrations reaching as high as 200 μg m –3 have been reported in transit regions in the vicinity of such thermal power plants. 34 In fact, the coupling between the BC concentrations and air mass origin, visualized using CWT maps ( Supporting Information Figure S3.c ), shows that BC at BCOB (although an order lower than expected in the vicinity of power plants; Supporting Information Figure S4 ) mostly arrived from the IGP.…”
Section: Resultsmentioning
confidence: 90%
“…PI is known to have significant emissions from C 4 -plants during this period, 38 40 while the coal combustion sources are smaller compared to the IGP. 12 , 32 34 We therefore judge the MCMC 3,C4 scenario to be the most fitting for MCOH, also since this implies a smaller change in the biomass source class contributions (up to 10% increase of C 4 -biomass) relative to BCOB, compared to the massive change in fossil fuel source class contributions (up to 27% increase in coal; MCMC 3,coal ) needed to be consistent with the isotope data. This conclusion is further corroborated by the FEG simulations, which suggest that the main potential geographical emission regions for MCOH during the winter period were a combination of PI and the IGP ( Supporting Information Figure S11 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were reported for thermal power plants in and around Delhi. A study conducted near thermal power plants of Singrauli concluded high BC concentration >200 µg/m 3 with peaks during early morning and evening hours, compared to the outside domain of the study region (Singh et al, 2018).…”
Section: Resultsmentioning
confidence: 80%
“…However, the marked reduction in surface NO 2 concentrations observed in Delhi and Ludhiana were not uniform across the IGP. Singrauli, a city with a number of large coal-fired power plants in its vicinity (Singh et al, 2018), recorded no significant reduction in surface NO 2 concentrations, i.e. the means over the period February 15-March 15 2020 and April 1-30 3030 were both 42 µg/m 3 , suggesting that the emissions from these plants were not reduced during the…”
Section: Climatological Surface No 2 Data Is Available For Delhi Backmentioning
confidence: 97%